Língua portuguesa e a expressão escrita de surdos - Silva, Eni Catarina da (2021)
Considering that the deaf have their own way of expressing themselves in the written modality, we assume as a general objective of the present study, to investigate the process of written expression of deaf people who have Libras (Brazilian Sign Language) as their first language (L1). In order to achieve this objective, in particular, from the analysis of texts produced by deaf people who participated in a university extension project offered by Federal University of Pará (UFPA), we proposed: to analyze the textual and discursive skills acquired and used by the deaf to produce meaning in writing texts; to analyze the functioning of language and interlanguage in the written production of these deaf people graduating from high school; and, identify and describe the patterns of regularity and/or occurrence, which govern the presentation and organization of information in the text of these deaf people. Regarding the theoretical and methodological framework, the study was based on a qualitative approach with a descriptive basis and adopted bibliographic and theoretical research as a methodological procedure. As a theoretical contribution, the present study was based on Riolfi (2019), Souza, Santos and Lendl (2017), Żaczek (2012), Fernandes (2003), Pereira (2014), among other reference works. Texts produced by deaf people who participated in the preparatory course for the Enem were used as a data collection instrument. Data collection took place from the contact with UFPA and was analyzed in the light of the theoretical framework. Understanding that, when expressing themselves in writing, the deaf uses their own language and leaves their characteristic marks on the text, a study on the functioning of the language used in texts written by deaf signers can contribute to the development of teaching strategies that enhance learning of written Portuguese (LP). The opportunity to contribute to enhance the quality of PL teaching and learning and to legitimize the deaf way of expressing themselves in writing is what justifies this research. In the search for a pattern of occurrence in the written production of the deaf and for a pattern of analysis, it was verified how the deaf mobilizes textual and discursive skills, in addition to describing the functioning of the language expressed in written productions in terms of linguistic levels. Considering lemmatization as a process of deflecting a word to determine its lemma, the analysis pointed to the use of a lemmatized vocabulary of Portuguese, organized in the structure of the syntax of Libras. It was also observed the existence of copies of parts of the motivating texts, in addition to the use of a domain vocabulary (prior knowledge of the deaf) of the PL etc. From the analysis of the three axes of integration of language practices of the National Common Curricular Base - BNCC, it was possible to observe that the texts written by the deaf showed marks of successive stages of interlanguage, which explains the representativeness in the lack of grammatical standards.